Drosophila center divider gene is expressed in CNS midline cells and encodes a developmentally regulated protein kinase orthologous to human TESK1. - Matthews, B.B.; Crews, S.T. (DNA and Cell Biology, 1999)
The Drosophila center divider gene (cdi) was isolated in an enhancer trap screen undertaken to identify genes involved in embryonic central nervous system (CNS) midline cell development. Three independent lines with P-element insertions at 91F were analyzed that all showed prominent beta-galactosidase expression in the CNS midline precursor cells and other cell types. Null mutations were created by imprecise P-element excision and shown to be larval lethal, although no severe CNS defects were observed in mutant embryos. The DNA surrounding the sites of insertion was cloned and found to contain a transcription unit that was dynamically expressed in a pattern corresponding to the enhancer trap line beta-galactosidase expression. Sequencing of cDNA clones revealed that the cdi gene encodes a 1140-amino acid protein that is an ortholog of the mammalian testis-specific TESK1 protein kinase. This serine/threonine kinase is distinct from other protein kinases because of sequence differences in the residues conferring substrate specificity. The unique sequence is conserved in Cdi, suggesting that Cdi/TESK1 represents a novel class of signaling proteins.